Quantum chromodynamics results from HERA and JLAB - Krüger, Katja (Pramāna, 2012)
Recent QCD results from electron-proton interactions at HERA and JLAB are presented. Inclusive cross-section measurements as well as studies of the hadronic final state like jet production or the production of heavy quarks are discussed. The results are compared with perturbative QCD predictions and their impact on the determination of the parton density functions of the proton as well as of the strong coupling α s is discussed.